2016
DOI: 10.1002/jcla.21889
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Propolis Against Yeasts Isolated From Blood Culture: In Vitro Evaluation

Abstract: This study demonstrated that propolis had significant antifungal activity against yeasts isolated from blood culture compared with FLU and ITR. The propolis MIC in azole-resistant strains such as C. glabrata was found lower than the FLU MIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 30 publications
(39 reference statements)
2
13
1
Order By: Relevance
“…Propolis, a natural product of honey bee, has been attracting the attention of researchers due to its various biological activities and therapeutic properties. Flavonoids, aromatic acids, diterpenic acids, and phenolic compounds appear as the principal components that are responsible for the biological activities of propolis samples [24]. Many studies have documented the remarkable action of propolis against viruses, parasites and many types of microorganisms (yeasts, and bacteria) [25].…”
Section: Resultsmentioning
confidence: 99%
“…Propolis, a natural product of honey bee, has been attracting the attention of researchers due to its various biological activities and therapeutic properties. Flavonoids, aromatic acids, diterpenic acids, and phenolic compounds appear as the principal components that are responsible for the biological activities of propolis samples [24]. Many studies have documented the remarkable action of propolis against viruses, parasites and many types of microorganisms (yeasts, and bacteria) [25].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have established the vast biological and pharmacolocial properties of propolis. The following medicinal properties have been found: antimicrobial 2628 , immunomudulatory 29 , antitumor 3032 , anti-inflammatory 3335 , antioxidant 3638 , antiviral 39,40 , antifungal 41,42 , and having hepatoprotective, nephroprotective and pancreatoprotective activities 4347 . Furtherore, recent studies have revealed that propolis affects hypoglycemic activity, which may positively impact diabetic complications.…”
Section: Introductionmentioning
confidence: 99%
“…Propolis has composed of wax 30%, resin and vegetable balsam 50%, essential and aromatic oils 10%, pollen 5%, and other substances (Tayeb and Sulaiman, 2014). Recently, the modern science has asserted that propolis has several effects and beneficial pharmacological such as antioxidative (Miguel et al, 2014), antimicrobial (Akca et al, 2016), antifungal (Sariguzel et al, 2015), antivirus (Schnitzler et al, 2010), antiinflammatory (Cavendish et al, 2015). On the other hand, Capucho et al (2012) found that propolis contains some minerals (Mg, Ca, I, K, Na, Cu, Zn, Mn and Fe), some vitamins (B1, B2, B6, C and E) and a number of fatty acids.…”
Section: Introductionmentioning
confidence: 99%